2017
DOI: 10.3847/1538-4357/aa9223
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Absorption of Surface Sausage and Surface Kink Modes under Photospheric Conditions

Abstract: We study the effect of resonant absorption of surface sausage and surface kink modes under photospheric conditions where the slow surface sausage modes undergo resonant damping in the slow continuum and the surface kink modes in the slow and Alfvén continua at the transitional layers. We use recently derived analytical formulas to obtain the damping rate (time). By considering linear density and linear pressure profiles for the transitional layers, we show that resonant absorption in the slow continuum could b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 62 publications
9
49
1
Order By: Relevance
“…Such energy structuring can be attributed to the presence of surface (pores 2, 3 and 4) and body (pores 1 and 5) mode waves, which have only recently been conclusively observed in photospheric imaging data [21]. Previous identifications of surface mode waves have come from theoretical estimations [17,18,58,59]. However, here we clearly show the existence of heightened wave energy towards the edges of the pore boundaries, which has only been made possible by the high spectral, spatial and temporal resolutions of our dataset coupled with modern spectropolarimetric inversion routines.…”
Section: Discussionmentioning
confidence: 99%
“…Such energy structuring can be attributed to the presence of surface (pores 2, 3 and 4) and body (pores 1 and 5) mode waves, which have only recently been conclusively observed in photospheric imaging data [21]. Previous identifications of surface mode waves have come from theoretical estimations [17,18,58,59]. However, here we clearly show the existence of heightened wave energy towards the edges of the pore boundaries, which has only been made possible by the high spectral, spatial and temporal resolutions of our dataset coupled with modern spectropolarimetric inversion routines.…”
Section: Discussionmentioning
confidence: 99%
“…External gas pressure enhancement -Requires β > 1 in the external medium which is not suitable for a coronal investigation. However, this may represent a flux tube located within the lower layers of the solar atmosphere (see, for example, Yu et al 2017). 2.…”
Section: Methodsmentioning
confidence: 99%
“…However, a radial gradient in the magnetic field strength can also provide the non-constant Alfvén speed profile that is required for a resonant layer to exist. To this end, many studies have demonstrated the mode conversion of MHD waves in the presence of a non-uniform magnetic field (see, for example, Ruderman & Erdélyi 2009;Antolin et al 2015;Giagkiozis et al 2016;Yu et al 2017;Howson et al 2017a). However, in the majority of previous studies, the magnetic field is simply a function of radial position and does not vary along the length of the magnetic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies of pore oscillations (Grant et al 2015;Moreels et al 2015a;Freij et al 2016) infer the surface/body characteristics of sausage modes using a combination of semiempirical models, theory, and the derived parameters of the modes from observations. Understanding the surface and body properties, however, is crucial in determining how energy is dissipated by modes in higher regions (Yu et al 2017b). Here, for the first time to our knowledge, we present conclusive, direct evidence for the existence of surface and body modes in photospheric pores supporting sausage modes.…”
Section: Introductionmentioning
confidence: 49%
“…As properties such as magnetic field and density vary rapidly from a pore to its surroundings, pores should support surface and body modes. Recent theoretical work (Yu et al 2017a(Yu et al , 2017b showed that resonant damping of slow surface sausage modes could be efficient under conditions usually observed in pores. Some previous studies of pore oscillations (Grant et al 2015;Moreels et al 2015a;Freij et al 2016) infer the surface/body characteristics of sausage modes using a combination of semiempirical models, theory, and the derived parameters of the modes from observations.…”
Section: Introductionmentioning
confidence: 99%